Ghana : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This Joint Staff Advisory Note of the Poverty Reduction Strategy Paper (PRSP) on Ghana reviews the Ghana Shared Growth and Development Agenda (GSGDA) for the period 2010-13. The GSGDA comprises three volumes: the policy framework, the costing framework, and the monitoring and evaluation framework; and follows Ghana Poverty Reduction Strategy I and II (GPRS-I and GPRS-II). IMF staff finds the underlying sector development plans compelling and well considered. However, important risks to implementation remain, which could reduce Ghana's ability to meet the GSGDA objectives.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet